Community‐based efforts to prevent obesity: Australia‐wide survey of projects. (8th August 2013) - Nichols, Melanie S.; Reynolds, Rebecca C.; Waters, Elizabeth; Gill, Timothy; King, Lesley; Swinburn, Boyd A.; Allender, Steven
Abstract : Issues addressed: Community‐based programs that affect healthy environments and policies have emerged as an effective response to high obesity levels in populations. Apart from limited individual reports, little is currently known about these programs, limiting the potential to provide effective support, to promote effective practice, prevent adverse outcomes and disseminate intervention results and experience. The aim of the present study was to identify the size and reach of current community‐based obesity prevention projects in Australia and to examine their characteristics, program features (e.g. intervention setting), capacity and approach to obesity prevention. Methods: Detailed survey completed by representatives from community‐based obesity prevention initiatives in Australia. Results: There was wide variation in funding, capacity and approach to obesity prevention among the 78 participating projects. Median annual funding was Au94 900 (range Au2500‐4.46 million). The most common intervention settings were schools (39%). Forty per cent of programs focused on a population group of 50 000 people. A large proportion of respondents felt that they did not have sufficient resources or staff training to achieve project objectives. Conclusion: Community‐based projects currently represent a very large investment by both government and non‐government sectors for the prevention of obesity. Existing projects are diverse in size and scope, and reach large segments of the population. Further work is needed to identify the full extent of existing community actions and to monitor their reach and future 'scale up' to ensure that future activities aim for effective integration into systems, policies and environments. So what?: Community‐based programs make a substantial contribution to the prevention of obesity and promotion of healthy lifestyles in Australia. A risk of the current intervention landscape is that effective approaches may go unrecognised due to lack of effective evaluations or limitations in program design, duration or size. Policy makers and researchers must recognise the potential contribution of these initiatives, to both public health and knowledge generation, and provide support for strong evaluation and sustainable intervention designs. Abstract : Community‐based programs have emerged as an effective response to high obesity levels in populations. This study investigated the size and reach of current community‐based obesity prevention projects in Australia to examine their characteristics, program features, capacity and approach to obesity prevention. The 78 participating projects covered a large proportion of the Australian population, although there was wide variation in the size, scope and approaches of the projects, and many were limited in duration or resources. Future progress in preventing obesity at the community level will require support for strong evaluation and sustainable intervention designs and progression towards more integrated policy‐ and systems‐based health promotion actions.